PENGARUH PEMBERIAN PUPUK BOKASHI JERAMI PADI DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI SAWAH (Oryza sativa L.) - Hamidah Midah (Universitas 17 Agustus 1945 Samarinda, 2011)
PENGARUH PEMBERIAN PUPUK BOKASHI JERAMI PADI DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI SAWAH (Oryza sativa L.) Effect of Paddy Straw Bokashi and Spacing on the Growth and Yield of Lowland Rice IR 64 Cultivare (Oryza sativa L.)HamidahFakultas Kehutanan, Universitas Widyagama Mahakam (UWGM) SamarindaSamarinda ABSTRACTThe research aimed at determining the effect of rate of paddy straw bokashi and plant spacing on the growth and yield of lowland rice. The research was conducted at Loh Sumber Village, Loa Kulu district, Kutai Kartanegara regency, from may to august 2008.The research design was split plot design arranged in Randomized Blok Design with 3 replications. The main plot was plant spacing consisted of 2 levels: J1 = 30 cm x 30 cm and J2 = 50 cm x 50 cm. The sub plot was paddy straw bokashi consisted of 5 levels: bo = no fertilizer application (control), b1 = 1,05 Kg bokashi square-1, b2 = 2,11 Kg bokashi square-1, b3 = 3,16 Kg bokashi square-1, b4 = 4,22 Kg bokashi square-1. Result of the research indicated that plant spacing treatment was significantly different on yield and highly significant different on plant height at 30 DAP, number of tiller per hill, number of filled grains, but it was not significantly different on plant height at 15 DAP, 45 DAP, time of harvest and weight of 1000 grains. The paddy straw bokashi treatment was significantly different on plant height at 30 DAP. The heighest yield was observed on the plant spacing treatment at 30 cm x 30 cm (j1) with 3.70 mgha-1. Key words : Paddy straw bokashi, Spacing, Lowland rice.